Analisis Industrial Robot Automotive Body Painting dengan Kendali Kinematik - Syarifuddin Syarifuddin; Anthonius L.S.Haans (Jurnal Teknik Mesin Sinergi, 2012)
The study aims to design and create a painting robot . kinematic equation of the 3 DOF .Cartesian robot was determined by using the equation method of DH parameter.Painting robot can replace human as the painting operator and can reduce the occurrence of respiratory distress due to inhalation whose physical form and movement mechanism resemble those of Cartesian one. The study concludes from the experiment with 3 DOF(three degrees of freedom) that Cartesian robot can do the painting on flat or corved plates for various field, on a surface of vehicle body. The prototype robot arm 3 DOF for automotive industry is an example outcome of the study.